From commitment to delivery: Implementation as the frontier for CAADP 3.0 - Ingabire, Chantal; Mkandawire, Richard; Nsimadala, Elizabeth; Omamo, Steven Were; Ulimwengu, John M. (International Food Policy Research Institute, 2025)
Africa enters the third phase of CAADP under the Kampala Declaration—CAADP 3.0—at a moment of profound possibility and significant stress. A young population, urban growth, technological adoption, and vibrant entrepreneurial systems are powerful drivers of agrifood innovation and transformation. Simultaneously, the continent’s agrifood systems are being shaped by intensifying climate shocks, constrained fiscal positions, fragile macroeconomic conditions, political volatility, and persistent conflict and displacement. These pressures are deepening hunger and undermining livelihoods across large regions. Importantly, Africa has accumulated considerable institutional knowledge and practical experience in policy formulation, planning, and cross-sector coordination. Governments, farmer organizations, regional bodies, and development partners understand the challenges facing the agrifood sector with far greater precision than in earlier CAADP cycles.